“The Philosophical and Emotional Dimensions of Love in Shakespeare’s Works” - Khasanova , Khadichabonu (DEVELOPMENT OF EDUCATION AND SCIENCE IN THE ERA OF DIGITAL TRANSFORMATION, 2025)
This article explores the theme of love in William Shakespeare’s works, delving into his nuanced portrayal of its beauty, complexity, and transformative power. Shakespeare presents love as a force that transcends social boundaries, defies logic, and ultimately reveals profound truths about human nature. Through famous sonnets and plays such as “Romeo and Juliet”, “A Midsummer Night's Dream”, and “Twelfth Night”, he illustrates love's paradoxes: its ability to bring joy and sorrow, clarity and confusion, fidelity and folly. The article examines Shakespeare’s use of poetic language and metaphors to convey the intensity of love's emotions, as well as the delicate balance he strikes between idealized and realistic representations of romantic relationships. By dissecting these elements, this work highlights how Shakespeare’s vision of love remains timelessly beautiful, resonating across centuries as both an artistic ideal and a reflection of the human experience